Manajemen Strategi Travel Haji dan Umrah dalam merekrut jamaah Umrah di PT. Bina Insani Madinah - Elsa Indah Rahayu; Hidayat HT; Muslimin Muslimin (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This thesis is entitled “Hajj and Umrah Travel Management Strategy in Recruiting Umrah Pilgrims at PT. Bina Insani Madinah City of Palembang” This research is focused on the implementation of marketing strategies at PT. Bina Insani Madinah in marketing Umrah worship packages. The purpose of this research is to find out the marketing strategy as well as the challenges and opportunities in implementing the recruitment strategy for the Umrah congregation of PT. Human Development Medina. This type of research is field research with a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews, and documentation. Miles and Huberman's data analysis technique with three stages, namely Data reduction, Data display, Conclusion drawing/verification. Furthermore, using marketing management theory (marketing mix) Edmund Jerome McCarthy. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that the management strategy for recruiting Umrah pilgrims from PT. Bina Insani Madinah is in line with the marketing mix strategy which has four components, namely first, the product strategy creates various Umrah package programs that vary according to market demand and prioritizes quality. Second, the pricing strategy by setting appropriate and competitive prices. Third, the location strategy by determining the location of the head office and branches that are strategic and have the potential to distribute products. Fourth, a promotion strategy that is more effective in recruiting Umrah pilgrims is priority partners and alumni of Umrah pilgrims. The challenges in recruiting Umrah pilgrims are business competition such as price, product, service quality competition and the lack of understanding and trust of the public towards Umrah travel agents. The opportunity has a good corporate image and is committed to providing quality services.